Human trafficking in Peru, analysis and perspective - Tejada Ortiz, Marco Aurelio (2016)
The crime of «human trafficking» involves a prohibited behavior related with the recruitment process, transport, transfer, reception or retention of a person in the territory of the country or passing through the country, for exploitation or other ilegal purposes which can be regarded validly as a new form of slavery, a transnational crime and even a crime against humanity by violating its perpetration enshrined human rights, specifically, the freedom, the dignity, the personal security, access to the justice, the right in order not to be subjected to slavery, the servitude, the forced labor, the right not to be subjected to torture, the right not to be subjected to gender violence, the freedom of circulation, the mental and physical health, the right to fair working and favorable conditions, the right to an adequate standard of living, the right to social security, and the right not to be sold or to be traded. Because of this, it is relevant the formation of a personal and functional appreciation of the punitive term «trafficking» , in order not only to identify, combat, punish, and eradicate this growing form of «organized crime», but especially in order to monitor the evolution that is achieving and that transcends the national scope and allowing to classify it as a «transnational organized crime».